2018
DOI: 10.1101/373670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activated αIIbβ3on platelets mediates flow-dependent NETosis via SLC44A2

Abstract: Platelet-leukocyte interactions are important for innate immune responses, but also contribute to the pathogenesis of thrombotic disorders, such as deep vein thrombosis. How these interactions are manifest and how they influence leukocyte function remains poorly understood. Here, we demonstrate that binding to von Willebrand factor under flow through glycoprotein Ib 'primes' platelets resulting in intracellular Ca 2+ release and  IIb  3 activation. This priming enables platelets to bind leukocytes via a mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 85 publications
3
9
0
Order By: Relevance
“…31,32 Slc44a2 deficient mice do however display reduced thrombus formation following flow restriction 57 where inflammatory cells from the blood, including neutrophils and platelets, are important contributors. 58,59 Moreover, it was recently demonstrated that platelets primed by VWF display-activated integrin α IIb β 3 (but not CD62P), which can then bind neutrophil SLC44A2 and mediate NETosis under venous flow, 60 suggesting that SLC44A2 is a mediator of cell-cell interactions. Therefore, we suggest incorporating the cellular compartment of the blood in further investigation of the effect of SLC44A2 on VT. To elucidate the contribution of SLC44A2 on the different cell types, cell specific knockouts of Slc44a2 might be interesting to include.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Slc44a2 deficient mice do however display reduced thrombus formation following flow restriction 57 where inflammatory cells from the blood, including neutrophils and platelets, are important contributors. 58,59 Moreover, it was recently demonstrated that platelets primed by VWF display-activated integrin α IIb β 3 (but not CD62P), which can then bind neutrophil SLC44A2 and mediate NETosis under venous flow, 60 suggesting that SLC44A2 is a mediator of cell-cell interactions. Therefore, we suggest incorporating the cellular compartment of the blood in further investigation of the effect of SLC44A2 on VT. To elucidate the contribution of SLC44A2 on the different cell types, cell specific knockouts of Slc44a2 might be interesting to include.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 NETosis requires platelets and may thus contribute to thrombosis. 38,39 Platelets express immune and inflammatory molecules such as interleukin-1 (IL1), 40 and a set of immune receptors including CD40L, Toll-like receptors (TLR), 31 and the Fc receptor for IgG FcRIIA 41 .…”
Section: Introductionmentioning
confidence: 99%
“…CTL2 gene SLC44A2 is well-established the human neutrophil antigen ( 37 ), and genetic risk factor for hearing loss, Meniere’s disease, and venous thrombosis ( 38 ). Neutrophil CTL2 could interact directly with platelets’ integrin α IIb β 3 and induce neutrophil extracellular trap (NETosis) that promotes thrombosis ( 39 ). SLC44A2 knockout mouse is protected against venous thrombosis showing that CTL2 could be an important therapeutic target for the disease ( 40 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%